Recollections - Arceo, Thelma M. (Quezon City : Ken Incorporated, 2013)
Collection of anecdotes in the author's personal diary about her son Ferdinand.
Keywords: Arceo, Ferdinand, -- 1952-1973 -- Anecdotes; Political activists -- Philippines -- Anecdotes